IMPROVING IT PERFORMANCE AT PT. FKS Multiagro, Tbk WITH A FRAMEWORK ITIL V.3 APPROACH BASED ON THE DMAIC METHOD - saputro, budi purnomo (AIBPM Publisher, 2022)
In an effort to provide better IT service and quality in order to support the company's course of business processes, the possibility of achieving the goals of IT service delivery are good and quality can not be achieved. One indicator of the achievement of the IT services is to achieve maximum satisfaction index internal users to use the IT services. Poor achievement index of user satisfaction can be caused by many factors, one of which is the performance of the IT organization. This study was conducted to know the things that affect the poor achievement index of user satisfaction in IT services and how to obtain the proper improvement, in terms of the service operation in the IT organization FKS Multiagro Conducted through focus group discussions with the management of the IT organization FKS Multiagro and the results obtained were analyzed with the DMAIC method by using a reference standard ITSM, ITIL v.3 frame work. The study concluded that poor achievement index of user satisfaction in IT services FKS Multiagro is caused by the absence in some instances, the lack of OLA and UC for all services, the absence of KEDB, no problem management, lack of configuration management, lack of incident information received through telephone, lack of training and no guidelines for prioritizing incidents.